2001
DOI: 10.1103/physrevlett.87.186808
|View full text |Cite
|
Sign up to set email alerts
|

Giant Magnetoresistance by Exchange Springs inDyFe2/YFe2Superlattices

Abstract: Magnetization and magnetoresistance measurements are reported for antiferromagnetically coupled DyFe 2 ͞YFe 2 multilayers in fields up to 23 T. It is demonstrated that the formation of short exchange springs (ϳ20 Å) in the magnetically soft YFe 2 layers results in a giant magnetoresistance as high as 32% in the spring region. It is shown that both the magnitude of the effect and its dependence on magnetic field are in good agreement with the theory of Levy and Zhang for domain wall induced giant magnetoresista… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…(Similar measurements of individual Co nanowires were made by Vila et al [276].) Walls of controlled size were formed in Co wires by growing them on a GdCo 1.6 substrate to create an exchange spring structure [302], a similar technique to that employed in the multilayers [243,245] discussed above in §4.3.2. This structure gives just the same sort of domain wall parallel to the interface, which these authors call a Zeeman domain wall, the thickness of which can be controlled by varying the applied field -in this paper the range studied was from 10 down to 5 nm thickness.…”
Section: Mesoscopic Devicesmentioning
confidence: 75%
See 2 more Smart Citations
“…(Similar measurements of individual Co nanowires were made by Vila et al [276].) Walls of controlled size were formed in Co wires by growing them on a GdCo 1.6 substrate to create an exchange spring structure [302], a similar technique to that employed in the multilayers [243,245] discussed above in §4.3.2. This structure gives just the same sort of domain wall parallel to the interface, which these authors call a Zeeman domain wall, the thickness of which can be controlled by varying the applied field -in this paper the range studied was from 10 down to 5 nm thickness.…”
Section: Mesoscopic Devicesmentioning
confidence: 75%
“…Just as in the DyFe 2 /YFe 2 multilayers [243], in-plane spring domain walls can be formed, although it was found that these played a rather minor role in the transport in this particular case. The MR was predicted based on the Valet-Fert model [76], with the angle between the Fe and Gd moments at the interface based on a simple micromagnetic model.…”
Section: Heterostructuresmentioning
confidence: 87%
See 1 more Smart Citation
“…However the MR is small ͑1.5%͒ and dominated by anisotropic magnetoresistance ͑AMR͒. Gordeev et al 3 demonstrated that the formation of short exchange springs in the YFe 2 / TbFe 2 superlattice results in a large magnitude of MR as high as 32%. In general, the directions of magnetization in consecutive layers can be switched when a magnetic field is applied, and MR changes dramatically as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…They display a rich variety of features, including exchange spring induced giant magnetoresistance. 9 But more features continue to be discovered. For example, X-ray Magnetic Circular Dichroism (XMCD) studies on a YFe 2 dominated DyFe 2 /YFe 2 system reveal complex magnetization reversal processes.…”
mentioning
confidence: 99%